Flutuação categorial entre advérbios e adjetivos com função adverbial - Gondim, Emanuela Monteiro (2020)
In this work, we establish a comparison of the uses of adverbs and adjectives with adverbial function in the 19th, 20th and 21st centuries, in order to elucidate this phenomenon in the light of the notion of categorical fluidity (Prototype Theory) and linguistic change. Our hypothesis is that: i) as they make up a larger category, that of modifiers, adjectives and adverbs are hybrid categories, of basic level, which contain elements whose characteristics are more strikingly related to the class of superordinate level, and tend, for this reason. motive, fluctuation; and ii) due to this fluctuation between adjectives and adverbs, some adjective forms have undergone, in more recent centuries, a process of linguistic change, tending to exercise the function of verbal modifier, but act in less contexts than adverbs in -ment. For the investigation of such hypotheses, we take as a corpus Brazilian theatrical plays from the 19th, 20th and 21st centuries, in which we select all occurrences of adverbs in - mente and adverbialized adjectives and analyze the possibility of correspondence between these forms. As in the literature (cf. HUMMEL, 2002a, 2002b, 2013), adverbial adjectives tend to be more recurrent in the oral modality, especially in informal records, the choice of the theater play genre is justified because it is the genre that most closely matches this modality . In addition, the Corpus do Português database was also used as a proof of the results we reached in the examination of the pieces. In this way, we analyze the results in two directions: from form to function and from function to form. Our data showed that adverbial adjectives, although they act more as qualifying adverbials in all periods and perform less diversified functions than forms in-modern, tend to expand their functions, acting as a modalizer, circumstantial and focuser. The data also pointed to the sharing of properties between adjectives and adverbs in the adverbial qualifier function, the one in which alternation was more frequent, which, among other factors, leads to proposing a modifier category, which would include the elements considered adjectives. and adverbs, organized by the prototype model.